Adiponectin regulates osteocytic MLO‐Y4 cell apoptosis in a high‐glucose environment through the AMPK/FoxO3a signaling pathway. Issue 10 (1st April 2021) - Zeng, Yuanyuan; Liang, Hengxing; Guo, Yue; Feng, Yunzhi; Yao, Qianqian
Abstract: Clinical studies have shown that persistent hyperglycemia following oxidative stress is associated with the apoptosis of osteocytes in diabetics. Adiponectin (APN) can ameliorate oxidative stress, and its receptors have been identified in bone‐forming cells. However, the relationship between APN and osteocyte apoptosis has not been fully elucidated. This study aimed to investigate whether APN could prevent osteocyte apoptosis and regulate reactive oxygen species (ROS) generation in a high‐glucose environment. Hoechst staining and fluorescence microscopy were used to observe the apoptosis of osteocytic MLO‐Y4 cells. Real‐time quantitative polymerase chain reaction and Western blot analysis were used to detect the expression of Caspase 3, Caspase 8, and Bcl‐2 . ROS generation was investigated with an active oxygen kit and fluorescence microscopy. Furthermore, the expression of proteins in the AMPK/FoxO3A signaling pathway was also studied by Western blot analysis. In a high‐glucose environment, APN promoted the proliferation of MLO‐Y4 osteocytes and the expression of Bcl‐2 but inhibited the expression of Caspase 3, Caspase 8, and ROS in a dose‐dependent manner. APN promoted the activation of p‐AMPK and p‐AMPK/AMPK, which reached their highest levels at 10 min and returned to baseline at 30 min. The expression of p‐FoxO3A/FoxO3A in both the cytoplasm and nucleus peaked at 15 min, and this expression was returned to baseline at 60 min. In summary, APN has an antiapoptotic effect and regulates ROS generation in MLO‐Y4 osteocytes in a high‐glucose environment. The AMPK/FoxO3A signaling pathway might be a key signaling pathway that participates in the effect of APN on regulating osteocyte apoptosis in diabetics. Abstract : Adiponectin has an antiapoptotic effect and regulates ROS generation in MLO‐Y4 osteocytes in a high‐glucose environment. The AMPK/FoxO3A signaling pathway might be a key signaling pathway that participates in the effect of Adiponectin on regulating osteocyte apoptosis in diabetics.